2006
DOI: 10.1088/0954-3899/32/5/008
|View full text |Cite
|
Sign up to set email alerts
|

Strange meson–nucleon states in the quark potential model

Abstract: The quark potential model and resonating group method are used to investigate the KN bound states and/or resonances. The model potential consists of the t-channel and s-channel one-gluon exchange potentials and the confining potential with incorporating the QCD renormalization correction and the spin-orbital suppression effect in it. It was shown in our previous work that by considering the color octet contribution, use of this model to investigate the KN low energy elastic scattering leads to the results whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…In this Letter, we report an observation of a pair of bands, which show several experimental features consistent with expectations for chiral doublet bands, in an odd-proton nucleus 123 I. Previous total-routhian-surface (TRS) calculations [13] and experimental investigations [13,14,15] have shown that this nucleus, as well as the other iodine nuclei, is very 𝛾soft, which ensures the possible occurrence of triaxial deformation. Chiral doublet bands in the case of iodine isotopes have been proposed in the odd-odd 118 I.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In this Letter, we report an observation of a pair of bands, which show several experimental features consistent with expectations for chiral doublet bands, in an odd-proton nucleus 123 I. Previous total-routhian-surface (TRS) calculations [13] and experimental investigations [13,14,15] have shown that this nucleus, as well as the other iodine nuclei, is very 𝛾soft, which ensures the possible occurrence of triaxial deformation. Chiral doublet bands in the case of iodine isotopes have been proposed in the odd-odd 118 I.…”
supporting
confidence: 80%
“…The experimental procedure and off-line analysis methods have been described at length in our previous publications. [14,15] A partial level scheme of 123 I is shown in Fig. 1, where the band labeled 3 is a new band identified in the present work.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, the 𝜋ℎ 11/2 ⊗ 𝜈ℎ 11/2 band does not follow the trend of a well-developed rotational band; in particular an unusual decrease followed by an unusual increase in level spacing is seen from the suggested 𝐼 = 14 to 18 levels in the 𝛼 = 0 sequence and seen from 𝐼 = 13 to 17 levels in the 𝛼 = 1 sequence. Very similar variations are also seen around spin 𝐼 = 𝑗+6 = 11/2 + 6 = 23/2 in the 𝜋ℎ 11/2 band in 123 I [1] and the 𝜈ℎ 11/2 band in 121 Te [19] and around spin 𝐼 = 6 in the 𝑔-band of the neighboring even-even Te isotopes. [19] Based on total-Routhian-surface (TRS) calculations, such a feature has been attributed [19] to an occurrence of a non-collective 𝛾 ≈ +60 ∘ (𝜋𝑔 7/2 ) 2 state which contributes 6 angular momentum to the total nuclear spin.…”
mentioning
confidence: 70%
“…The structure and properties of the S 01 resonance Λ(1405), discovered in 1960's, is still one of the puzzling issues in hadron physics. In the literature the Λ(1405) is considered as an s-channel resonance [1] or as a quasi-bound ( KN, Σπ) state [2][3][4][5][6][7][8][9][10][11][12][13]. In quark-model approaches, this hyperon is treated as a pure |qqq -state [14][15][16][17][18][19][20], or still as an admixture of |q 3 +q 4 q configuration [21,22].…”
Section: Introductionmentioning
confidence: 99%